IMPLEMENTATION OF BINNENDIFFERENZIERUNG IN WRITING FOR GERMAN LEARNERS AS DAF - Julaikah, Dwi Imroatu; Mustofa, Ali; Titaley, Audrey; Rusmiyati; Ridwan, Agus; Bingku, Soflies Marry E. (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
German is widely taught as a foreign language (DaF; Deutsch als Fremdsprache) in Indonesia. However, observations during German language instruction at Universitas Negeri Surabaya (UNESA) have revealed that writing skills pose a significant challenge for many learners. Preliminary observations suggest that diverse language proficiency levels is a primary contributing factor to this challenge. Notably, a substantial portion of German Education students at UNESA did not have prior German language course’s exposure in high school. In light of these observations, the present study underscores the urgency of implementing Binnendifferenzierung, a differentiated instruction approach, to address the diverse skill levels among learners. This qualitative descriptive research aims to describe the implementation of Binnendifferenzierung—differentiation learning—in the "Thematisches Schreiben" (Thematic writing) course. The study employed one form of differentiation: Differenzierung nach Aufgaben (task differentiation). Differenzierung nach Aufgaben involved introducing two variations of writing exercises at the A2 level: Aufgabe A. These variations included (a) vocabulary enrichment exercises, (b) guided writing with keywords, (c) serial writing based on cartoon images, and (d) free-theme writing. Differenzierung nach Sozialformen involved differentiating the teaching methods based on learners’ preferences and learning styles. The findings of the study demonstrate that the implementation of Binnendifferenzierung in both forms effectively accommodated the heterogeneity of learners and provided opportunities for individualized learning tailored to their interests and abilities. This approach also introduced variations that aligned with the diverse needs of the learners.